Software Still As Much an Art As Science. - Humelsine, Jim (Communications of the ACM, 2010)
A letter to the editor is presented in response to the article "Retrospective: An Axiomatic Basis for Computer Programming," by C. A. R. Hoare in the October 2009 issue.